2020
DOI: 10.1101/2020.04.17.047472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of functionally-distinct macrophage subpopulations regulated by efferocytosis inDrosophila

Abstract: Macrophages are a highly heterogeneous population of cells, with this diversity stemming in part from the existence of tissue resident populations and an ability to adopt a variety of activation states in response to stimuli. Drosophila blood cells (hemocytes) are dominated by a lineage of cells considered to be the functional equivalents of mammalian macrophages (plasmatocytes). Until very recently plasmatocytes were thought to be a homogeneous population. Here, we identify enhancer elements that label subpop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Consistent with this, a study provided molecular evidence of Drosophila macrophages taking on an alternatively activated (M2) status in response to local cues in tissue regeneration ( Neves et al, 2016 ). Single cell RNA sequencing and functional studies further support the hypothesis of distinct activation states in Drosophila macrophages, identifying subpopulations that have differential involvement in phagocytosis, metabolic homeostasis, and the humoral AMP response ( Cattenoz et al, 2020 ; Cho et al, 2020 ; Coates et al, 2020 ; Fu et al, 2020 ; Ramond et al, 2020a ; Shin et al, 2020 ; Tattikota et al, 2020 ). Functional distinctions are driven by developmental stage ( Cattenoz et al, 2020 ; Cho et al, 2020 ), injury, and immune challenge ( Coates et al, 2020 ; Fu et al, 2020 ; Ramond et al, 2020a ; Tattikota et al, 2020 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Consistent with this, a study provided molecular evidence of Drosophila macrophages taking on an alternatively activated (M2) status in response to local cues in tissue regeneration ( Neves et al, 2016 ). Single cell RNA sequencing and functional studies further support the hypothesis of distinct activation states in Drosophila macrophages, identifying subpopulations that have differential involvement in phagocytosis, metabolic homeostasis, and the humoral AMP response ( Cattenoz et al, 2020 ; Cho et al, 2020 ; Coates et al, 2020 ; Fu et al, 2020 ; Ramond et al, 2020a ; Shin et al, 2020 ; Tattikota et al, 2020 ). Functional distinctions are driven by developmental stage ( Cattenoz et al, 2020 ; Cho et al, 2020 ), injury, and immune challenge ( Coates et al, 2020 ; Fu et al, 2020 ; Ramond et al, 2020a ; Tattikota et al, 2020 ).…”
Section: Discussionmentioning
confidence: 83%
“…A recent body of research suggests that not all macrophages are equal, rather they can be categorized into phenotypically and functionally unique subpopulations. Single cell RNA sequencing and functional studies in Drosophila identify transcriptionally and functionally distinct clusters of plasmatocytes, which are modulated by developmental time, lineage, injury, and infection status ( Cattenoz et al, 2020 ; Cho et al, 2020 ; Coates et al, 2020 ; Ramond et al, 2020a ; Tattikota et al, 2020 ). Vertebrate single cell studies identify similar heterogeneity among macrophages, modulated by developmental stage and lineage ( Gordon and Taylor, 2005 ; Martinez et al, 2006 ; Paul et al, 2015 ; Lin et al, 2019 ; Lantz et al, 2020 ).…”
Section: New Insights Into Macrophage Diversitymentioning
confidence: 99%
“…Single cell RNA sequencing studies have shown that blood cell populations may be more complicated in Drosophila than previously anticipated ( Cattenoz et al, 2020 ; Cho et al, 2020 ; Tattikota et al, 2020 ). At present these approaches are limited to larval stages, although recent work suggests that subpopulations of functionally-distinct macrophages may also exist in the developing fly embryo ( Coates et al, 2020 ). The expression of Spitz under the control of TinC-GAL4 corroborated midline efferocytosis defects and revealed that macrophage-specific expression was not necessary for an impact on this behavior.…”
Section: Discussionmentioning
confidence: 99%